Effect of marathon training on the plasma lactate response to submaximal exercise in middle-aged men. Issue 1 (March 1988) - Rumley, A G; Taylor, R; Grant, S; Pettigrew, A R; Findlay, I; Dargie, H
Abstract : Twenty-one previously sedentary male volunteers (aged 35-50 years) undertook a defined marathon training programme lasting 30 weeks. At weeks 0 (T1), 15 (T2) and 30 (T3) they underwent measurement of maximal oxygen uptake (VO2 max), submaximal VO2 and submaximal plasma lactate concentration during cycle ergometry. No exercise was taken for 24-48 hours prior to testing. During training aerobic power increased significantly (p less than 0.001) from an initial VO2 max at T1 of 33.9 +/- 6 (mean +/- sd) ml.kg-1min-1 to 39 +/- 5.6 ml.kg-1min-1 at T2 but the T3 value of 39.2 +/- 5.2 ml.kg-1min-1 was not significantly different from that at T2. Plasma lactate concentration of 4 mmol.l-1 (OBLAw) occurred at a significantly (P less than 0.05) higher workload (155 +/- 28 w) at T2 compared with T1 (132 +/- 30 w) but the T3 figure was 137 +/- 34 w. OBLA VO2 at T1 was 2.04 +/- 0.42 l.min-1, at T2 was 2.24 +/- 0.04 l.min-1 but at T3 was 2.03 +/- 0.30 l.min-1 (T1:T2 P less than 0.05, T1:T3 NS). OBLA % VO2 max at T1 was 75 +/- 12%, at T2 was 73 +/- 11% but at T3 was 62 +/- 10% (T1:T2 NS, T1:T3 P less than 0.01).